Synthesis and bioassay of rationally designed DXR inhibitors as potential antimalarial lead compounds - Nokalipa, Iviwe Cwaita (Rhodes University, Faculty of Science, Department of Chemistry, 2017)
Globally, the eradication of malaria has been challenging due to the problem of resistance that past and currently available drugs exhibit. This is exacerbated by the inherent need for anti-malarial drugs to be affordable to the poverty-stricken majority that is primarily affected by this burden. This research has focused on the development of potential inhibitors of 1-deoxy-D- xylulose-5 phosphate reductoisomerase (DXR), an essential enzyme in the mevalonate- independent pathway for the biosynthesis of isoprenoids in Plasmodium falciparum. DXR mediates the isomerisation and reduction of 1-deoxy-D-xylulose-5-phosphate into 2-C- methyl-D-erithrytol 4-phosphate. This enzyme has been determined to be a target for the development of novel antimalarial agents and extensive molecular modelling has been undertaken to develop inhibitors that fit into the DXR active site. The in silico docking data have been used to inform the design and synthesis of various N-benzyl-substituted phosphoramidate ligands that were determined to have potential as novel substrate mimics of fosmidomycin, a known DXR inhibitor. Synthesis of the N-benzyl-substituted phosphoramidate ligands involved a nine-step sequence commencing from diethyl phosphoramidate. In all, some 40 compounds have been prepared, some of them new, and were fully characterized using NMR. Attention has also been given to the mass spectrometric fragmentation patterns exhibited by selected intermediates. Four of the final products were evaluated for in vitro antimalarial activity using a PLDH assay and exhibited IC50 values < 100 ÂµM.
Keywords: Uncatalogued